Self-regulatory employability attributes and competency: the strengthening role of grit - Ismail, Sadika; Potgieter, Ingrid L.; Coetzee, Melinde (Frontiers in Psychology, 2023)
This study examines grit as psychological mindsets that explain the link between self-regulatory employability attributes and perceived employability competency expectations in a sample of South African adults (N=308). A quantitative, cross-sectional research design approach was used to collect primary data. Results of a mediation analysis through structural equation modelling revealed grit as an important mechanism to strengthen the association between employability attributes (career agility, cultural ingenuity, proactive career resilience) and employability competency expectations (autonomy/leadership skills and personal employability qualities). This study makes an important contribution to the role of learning and training through understanding the role of grit in enhancing prospects of employability. This study further adds to the grit literature, highlighting the role that grit plays in the contemporary employment context. Practical implications include supportive practices that strengthen individual workers' grit when confronted with the turbulent changes of today's work world. 1 Introduction Today's work world demands continuous upskilling and reskilling resulting from the rapid pace of technological changes which necessitates further education and training for sustained employability